THE MICROPROCESSOR DEVICE FOR MEASUREMENT OF HUMIDITY OF LOOSE MATERIALS (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2024)
The optimal method for creating a universal system for most materials is the ultrahigh-frequency moisture measurement method. The article discusses the generalized structure of a humidity meter. The system is designed to solve all problems related to obtaining measurement information about the moisture content of bulk materials and products of its processing.